Flood Disaster Risk Management In Manado City - Candra, Yohanes; Maarif, Syamsul; Kusuma, Kusuma; wilopo, wilopo (CV. AFDIFAL MAJU BERKAH, 2024)
Geological and hydrometeorological disasters are disasters that are often experienced by every region in Indonesia. Hydrometeorological disasters such as floods are influenced by strong westerly winds and world climate change. Apart from that, inappropriate land conversion is also one of the factors causing this disaster. One of the regions in Indonesia that is highly vulnerable to flood disasters is the city of Manado. Geographically, Manado City is surrounded by mountains and 5 large rivers that pass-through Manado City, namely the Tikala river and the Tondano river which merge in the Paal 2 area, the Malalayang river, the Sario River and the Bailang River. To overcome this disaster, it is necessary to carry out appropriate mitigation efforts to minimize the impact caused by the flood disaster in Manado City. The aim of this research is to analyze the risk level of flood disasters in Manado City and provide appropriate recommendations related to flood disaster mitigation in Manado City. This research uses analysis with quantitative descriptive research methods. The results of this research are that there are 3 classes of flood disaster risk levels in Manado City. In the high class there are 53 subdistricts, medium 2 subdistricts and low 32 subdistricts. Policy recommendations are made based on the level of risk by taking into account the main causal factors. Furthermore, it is recommended in every sub-district.